2004
DOI: 10.1007/s00221-004-2127-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in rapid muscle activation after rate of force development training of the elbow flexors

Abstract: In young adults, improvements in the rate of force development as a result of resistance training are accompanied by increases in neural drive in the very initial phase of muscle activation. The purpose of this experiment was to determine if older adults also exhibit similar adaptations in response to rate of force development (RFD) training. Eight young (21-35 years) and eight older (60-79 years) adults were assessed during the production of maximum rapid contractions, before and after four weeks of progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
3
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 34 publications
10
61
3
5
Order By: Relevance
“…In line with this, Duchateau and Baudry (2014) presented extensive evidence that training-related increases in the rate of force production (i.e., RFD) during ballistic contractions primarily resulted from adaptations in motor unit discharge rate. These conclusions underscore the critical role of maximal motor unit discharge rate (i.e., muscle activation) on the ability to rapidly develop force, and are consistent with research showing that explosivetype training elicits increases in high-frequency motor unit discharges at the onset of muscular contraction (Van Cutsem et al 1998) and research showing strong relationships between changes in RFD and changes in the rate of EMG amplitude rise (RER; ∆EMG/∆time) after periods of resistance-type training (Aagaard et al 2002;Barry, Warman and Carson 2005;Blazevich et al 2008).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…In line with this, Duchateau and Baudry (2014) presented extensive evidence that training-related increases in the rate of force production (i.e., RFD) during ballistic contractions primarily resulted from adaptations in motor unit discharge rate. These conclusions underscore the critical role of maximal motor unit discharge rate (i.e., muscle activation) on the ability to rapidly develop force, and are consistent with research showing that explosivetype training elicits increases in high-frequency motor unit discharges at the onset of muscular contraction (Van Cutsem et al 1998) and research showing strong relationships between changes in RFD and changes in the rate of EMG amplitude rise (RER; ∆EMG/∆time) after periods of resistance-type training (Aagaard et al 2002;Barry, Warman and Carson 2005;Blazevich et al 2008).…”
Section: Introductionsupporting
confidence: 81%
“…The greater MVIC trial was used to normalize the muscle activation during the bench press throws. EMG data were analyzed over the following time intervals: pre100-pre50 ms, pre50-0 ms (where 0 corresponds to the movement onset), 0-50 ms, 50-100 ms and 100-150 ms. Additionally, the normalized change in RMS EMG between the different time intervals was used as a measure of the rate of EMG rise (RER) (Aagaard et al 2002;Barry, Warman and Carson 2005;Blazevich et al 2008). All data were stored for offline analysis with custom-built software (LabView, National Instruments, Austin, Texas).…”
Section: Assessment Of Emg Activitymentioning
confidence: 99%
“…2). The rate of EMG rise (RER; % PEMG s -1 ) was used to examine the rate of muscle activation (Clark et al 2011(Clark et al , 2013Mitchell et al 2011) and was calculated as the linear slope of the normalized EMG-time curve at time intervals of 30 ms (RER30), 50 ms (RER50), and 75 ms (RER75) from onset similar to the procedures described by Aagaard et al (2002) and Barry et al (2005). The specific time intervals for determining RER (in particular the selection of 75 ms instead of 100 ms) were used because of a characteristic decrease in the EMG signal amplitude occurring at~80-100 ms following the signal onset (Aagaard et al 2002; Note: RER time intervals do not correspond directly to the RFD intervals due to the electromechanical delay.).…”
Section: Electromyography Measurementsmentioning
confidence: 99%
“…Such an increase in the quantity of activated muscle can result from an increase in descending neural drive to the pool of spinal motoneurons. It is not surprising, therefore, that a higher RFD can be seen in individuals who have the highest rise in neuromuscular activity [largest rates of electromyographic (EMG) rise] at contraction onset, 12,13 that strength training leading to an increased and more rapid rate of neuromuscular activity (EMG) is accompanied by increases in contractile RFD, 1,5,8,26,29 and that the greater presence of doublet motor unit firing patterns induced by strength training is associated with greater RFD. 29 In a recent study we showed that increases in RFD resulting from longer-term (10 weeks) strength training were well related to increases in neuromuscular activity; however, we were unable to explain the increases in RFD after shorter-term (5 weeks) training.…”
mentioning
confidence: 99%